Need analysis of Character Education-Based Digital Comic Instructional Material in English Learning for Elementary School Teachers - Ika Sulistyarini; Sri Kadarwati; Edi Prayitno (Journal on Education, 2022)
This research aims to present the results of the need analysis of digital comic instructional material based on character education in English learning for elementary school teachers. The data in this research were collected through observations and in-depth interviews with four English tutors for elementary school UPBJJ UT Semarang teachers and fifty students taking English classes for elementary school teachers for the 2022.2 registration period. The data obtained was then analyzed using descriptive analysis. The result of the research shows that tutors and students require digital comic instructional material based on character education in learning English for elementary school teachers. It can be concluded that digital comic instructional material focused on character education in English learning for elementary teachers is crucial. It follows that digital comic instructional material focused on character education in English learning for elementary teachers is very necessary.